2016
DOI: 10.1103/physreve.94.022218
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties of the soft-wall elliptical billiard

Abstract: Physical systems such as optical traps and microwave cavities are realistically modeled by billiards with soft walls. In order to investigate the influence of the wall softness on the billiard dynamics, we study numerically a smooth two-dimensional potential well that has the elliptical (hard-wall) billiard as a limiting case. Considering two parameters, the eccentricity of the elliptical equipotential curves and the wall hardness, which defines the steepness of the well, we show that (1) whereas the hard-wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Our results assist to develop the theory of PI quantum scarring further as well as to understand the connection between PI scars and related phenomena such as conventional scarring [6,7] and branched flow [40]. Moreover, for classical billiards it has been shown that soft boundaries can bring chaos [36]. In addition, an external magnetic field can cause chaotic behavior [37].…”
Section: Discussion and Summarymentioning
confidence: 67%
See 1 more Smart Citation
“…Our results assist to develop the theory of PI quantum scarring further as well as to understand the connection between PI scars and related phenomena such as conventional scarring [6,7] and branched flow [40]. Moreover, for classical billiards it has been shown that soft boundaries can bring chaos [36]. In addition, an external magnetic field can cause chaotic behavior [37].…”
Section: Discussion and Summarymentioning
confidence: 67%
“…Moreover, for classical billiards it has been shown that soft boundaries can bring chaos. 36 In addition, an external magnetic field can cause chaotic behavior. 37 It has been hypothesized 41 that the softness of the wall combined with a magnetic field causes fractal behavior of the magnetocondutance observed in semiconductor quantum cavities.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A less studied billiard is the "soft" version, where the boundary of the billiard table Q is defined by a finite potential wall V , with V (x, y) = 0 for (x, y) ∈ int(Q) and V (x, y) ∈ (0, ∞) for (x, y) ∈ ∂Q. In such a setting, for a Sinai (dispersing) billiard [12,17], the existence of a stable island around a periodic orbit which is tangent to the billiard's wall (or near the corner) was found numerically in [22]; see also [23,24] for other examples of such soft billiards.…”
Section: Introductionmentioning
confidence: 99%